2013
DOI: 10.1074/jbc.m113.460832
|View full text |Cite
|
Sign up to set email alerts
|

AMP-dependent Kinase Inhibits Oxidative Stress-induced Caveolin-1 Phosphorylation and Endocytosis by Suppressing the Dissociation between c-Abl and Prdx1 Proteins in Endothelial Cells

Abstract: Background: Oxidative stress increases vascular permeability though caveolin-1 phosphorylation. The exact role of AMPK is unknown. Results: AMP-dependent kinase (AMPK) inhibits caveolin-1 phosphorylation by stabilizing the interaction between c-Abl and Prdx-1. Conclusion: AMPK activation inhibits oxidant induced-vascular permeability.Significance: The present study shows a novel protective role of AMPK in the vascular homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 54 publications
2
30
0
Order By: Relevance
“…This study showed that H 2 O 2 exposure induced the phosphorylation of Cav-1, which resulted in endothelial barrier disruption [19]. Further research also confirmed the induction of Cav-1 following oxidative stress and the fundamental role of Cav-1 in endothelial barrier function [20]. It also has been shown that caveolae and Cav-1 may play an important role in the mediation of native and modified LDL uptake/efflux and transcytotic trafficking in ECs [21].…”
Section: Discussionmentioning
confidence: 92%
“…This study showed that H 2 O 2 exposure induced the phosphorylation of Cav-1, which resulted in endothelial barrier disruption [19]. Further research also confirmed the induction of Cav-1 following oxidative stress and the fundamental role of Cav-1 in endothelial barrier function [20]. It also has been shown that caveolae and Cav-1 may play an important role in the mediation of native and modified LDL uptake/efflux and transcytotic trafficking in ECs [21].…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have shown that AMPK participates in regulation of angiogenesis and function of endothelial cells [18, 19]. However, the precise role of AMPK in this aspect is rather controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Several regulatory mechanisms of Cav-1 phosphorylation have been identified. Under oxidative stress, AMPK inhibits Cav-1 phosphorylation and endocytosis (168). Cav-1 phosphorylation at Tyr (14) following LPS exposure promotes Cav-1 and TLR4 interaction leading to NF-κB activation and generation of proinflammatory cytokines (77,88).…”
Section: Translational Regulationmentioning
confidence: 99%